Accelerated DNA methylation age and the use of antihypertensive medication among older adults - Gao, X.; Colicino, E.; J. Shen; Just, A. C.; Nwanaji-Enwerem, J. C.; C. Wang; Coull, B.; X. Lin; Vokonas, P.; Zheng, Y.; Hou, L.; Schwartz, J.; et al. (Aging (Albany NY), 2018)
The discrepancy of DNA methylation age (DNAmAge) with chronological age (termed as age acceleration, AA) has been identified to be associated with many aging-related health outcomes including hypertension. Since taking antihypertensive medication (AHM) could prevent aging-related diseases caused by hypertension, we hypothesized that using AHM could also reduce the AA. We examined this hypothesis among 546 males aged 55-85 years by exploring the associations of AHM use with AA and its change rate (DeltaAA) in two visits with a median follow-up of 3.86 years. Horvath DNAmAge was derived from DNA methylation profiles measured by Illumina HumanMethylation450 BeadChip and information on AHM use was collected by physician interview. A general decreasing pattern of AA was observed between the two visits. After the fully adjusting for potential covariates including hypertension, any AHM use showed a cross-sectional significant association with higher AA at each visit, as well as a longitudinal association with increased DeltaAA between visits. Particularly, relative to participants who never took any AHM, individuals with continuous AHM use had a higher DeltaAA of 0.6 year/chronological year. This finding underlines that DNAmAge and AA may not be able to capture the preventive effects of AHMs that reduce cardiovascular risks and mortality.
Keywords: Aged *Aging Antihypertensive Agents/classification/*therapeutic use DNA Methylation/*physiology Humans Hypertension/*drug therapy *DNA methylation age *antihypertensive medication *epigenetic epidemiology *hypertension